Competence in Program Evaluation and Research Assessed by State School Counselor Licensure Examinations. (January 2018) - Carey, John C.; Martin, Ian; Harrington, Karen; Trevisan, Michael S.
This study investigated how state licensure examinations address school counseling program evaluation and research. In the 31 states that require them, examinations gave little attention to measuring competencies associated with designing and conducting a program evaluation. We found variability in how these examinations addressed research competencies. These results indicate a need for greater clarity and understanding on the part of state examiners regarding what school counselors need to know and be able to do in terms of program evaluation and research.